2013
DOI: 10.17265/1934-7391/2013.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of Plasmodium malariae-falciparum Co-Infection by Molecular Speciation in Bangolan, North West Region of Cameroon

Abstract: Abstract:Although microscopy still remains the gold standard for the diagnosis of malaria, rapid diagnostic tests (RDTs) and PCR assays have been shown to be sensitive and specific. Very few comparative studies have been reported of the three diagnostic methods on the same samples in vulnerable groups. Microscopy, RDTs and PCR assays were used for detection and speciation of Plasmodium falciparum (Pf), Plasmodium malariae (Pm) and Plasmodium ovale (Po) in patients in a rice culture savanna ecotype. Fifty four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
0
1
Order By: Relevance
“…Contrary to results obtained by Cho-Fru et al [29] that reported on the presence of substantial numbers of Plasmodium vivax cases in the same study area, no cases of vivax malaria were observed. The results differ from those obtained by Achonduh et al [30] in Bangolan where a higher proportion of Plasmodium malariae was observed compared to Plasmodium Ovale . This shows an inverse relationship between the prevalence of ovale and malariae in the Guinea savanna region of Bangolan and the littoral forest region of Mutengene.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to results obtained by Cho-Fru et al [29] that reported on the presence of substantial numbers of Plasmodium vivax cases in the same study area, no cases of vivax malaria were observed. The results differ from those obtained by Achonduh et al [30] in Bangolan where a higher proportion of Plasmodium malariae was observed compared to Plasmodium Ovale . This shows an inverse relationship between the prevalence of ovale and malariae in the Guinea savanna region of Bangolan and the littoral forest region of Mutengene.…”
Section: Discussioncontrasting
confidence: 99%